2021
DOI: 10.1017/s0144686x21000350
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the shrinking world: dementia, localisation and neighbourhood

Abstract: ‘Dementia-friendly communities’ herald a shift toward the neighbourhood as a locus for the care and support of people with dementia, sparking growing interest in the geographies of dementia care and raising questions over the shifting spatial and social experience of the condition. Existing research claims that many people with dementia experience a ‘shrinking world’ whereby the boundaries to their social and physical worlds gradually constrict over time, leading to a loss of control and independence. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 65 publications
5
30
0
Order By: Relevance
“…Rather than being passive in the face of these challenges, we found that participants showed considerable creative resilience and active coping. In terms of the literature and concepts referenced in our introduction, they were 'active social agents', 7 'pushed back' in multiple ways 17 and adopted a wide variety of emotional coping strategies. 18 We maintain that it is important not just to understand the challenges that people with dementia faced during the pandemic but also the ways in which they acted for themselves, and others, and the facilitators and barriers they encountered in doing so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than being passive in the face of these challenges, we found that participants showed considerable creative resilience and active coping. In terms of the literature and concepts referenced in our introduction, they were 'active social agents', 7 'pushed back' in multiple ways 17 and adopted a wide variety of emotional coping strategies. 18 We maintain that it is important not just to understand the challenges that people with dementia faced during the pandemic but also the ways in which they acted for themselves, and others, and the facilitators and barriers they encountered in doing so.…”
Section: Discussionmentioning
confidence: 99%
“…16 This wider literature includes research that considers how people with dementia interact with their local community and neighbourhood. Notably, Ward et al 17 argue that Duggan et al's 12 'shrinking world' concept provides a 'partial and unhelpfully negative picture of neighbourhood life that reinforces ideas of the passivity of people with dementia'. Based on qualitative research with 67 people with dementia conducted before the pandemic (2014-2019), Ward et al found that people with dementia commonly 'push back', including by trying to protect loved ones from the demands of their condition, engaging in reciprocal exchange, building new social networks, challenging or resisting negative stereotypes through visibility in public spaces or through social contribution, adapting how they traverse their neighbourhood, seeking to maintain habitual spatial practices, and by actively drawing upon neighbourhood resources.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…This discrepancy includes two important variables: transportation, namely, if participants are driving a car themselves, and whether they use a public transportation service. It has earlier been pointed out that driving cessation following dementia usually has consequences for the persons’ participation in places outside home ( Ward et al, 2021 ). The availability of transportation options to different places in the community and location of services would therefore be of interest to explore in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the resulting combined sample provides an opportunity to closely examine stability and change in participation in places outside home. As recommended by Ward et al (2021) , including data from multiple countries allows location to be taken into account in investigation of participation, rather than merely focusing on disease symptoms. Although contextual socio-environmental data in the four countries were not explicitly collected, the similarities and differences of out-of-home participation among people with dementia in the four countries would provide valuable insights, and generate research questions and relevant methods for future investigations.…”
Section: Methodsmentioning
confidence: 99%
“…Familiarity with a place may thus increase over time and then decline with deteriorating cognitive and physical functioning (Burns, Lavoie, and Rose 2012). Other scholars have challenged an “impairment-led” explanation for the experience of a “shrinking world”: People with dementia, they argue, recreate their neighborhood through habitual practices, concentrating more time in certain places, allowing them to “hold on to familiarity” (Ward et al 2021:9). These people are not prevented from developing familiar relationships altogether, but the space for doing so has been reduced.…”
Section: What Threatens Familiarity?mentioning
confidence: 99%